Legal Comparison against the Death Penalty Sanctions regulated in the Positive Laws of Indonesia and China - Kesuma Irdini (Faculty of Law, Universitas Lampung, 2021)
Corruption is a severe problem worldwide, so it takes a strict rule of law and strong law enforcement efforts to eradicate it. China's legal system has proven to be effective in reducing corruption among state officials. One of China's anti-corruption efforts is to impose harsh penalties on perpetrators, including the death penalty. In light of this success, this study will conduct a legal comparison with the death penalty, which is regulated in Indonesian and Chinese positive law. The type of research used is normative juridical with a conceptual and statute approach. The data processed in this study include primary data and secondary data with data collection techniques and management using a literature review. The findings of this study highlight the threat of the Death Penalty, as outlined in Article 2 Paragraph (2) of the Corruption Crime Act, which focuses on corrupt acts committed under certain conditions. In Indonesia, no one has ever been sentenced to death for corruption. The People's Republic of China's Criminal Law of the death penalty threat has existed since 1900 AD. Article 383 of the Chinese Criminal Code stipulates that anyone who accepts bribes is subject to the death penalty. A significant difference from this Comparison lies in the classification of capital punishment with a corruption amount of more than 50,000 Yuan and for bribery cases in Chinese regulations. Meanwhile, there is no such regulation in Article 2 paragraph (2) of the Indonesian Corruption Laws.